Evaluating the potential of Lampam sub-sistrict to be developed as a conservation tourist destination - Sirinart Kanjanopas (Prince of Songkla University, 2006)
Thessis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2006